Problematique approach to analyse barriers in implementing industrial ecology in Philippine industrial parks - Promentilla, Michael A. B. (Animo Repository, 2016)
Industrial ecology is recognized as an important framework toward a circular economy wherein industrial systems minimize their environmental burden by mimicking the material cycles and energy cascades found in biological ecosystems. Advocates of such framework in planning of eco-industrial parks suggest that both economic and environmental gains can be attained by transforming the industrial production from a linear to a closed loop system. However, it is imperative first to understand and analyze systematically the barriers in implementing the concept of industrial ecology in industrial parks even at the early planning stage. This work thus proposes a problematique approach to understand and analyse such barriers toward a successful development of eco-industrial parks. A problematique is a term coined by Warfield referring to concepts and tools for a structural model of relationships among members of a set of problems. The problematique is shown to be effective in analyzing the structure that underlies problematic situations, thus increasing the potential for crafting solution through human intervention. An illustrative case study was presented using a methodological framework built from Decision Making Trial and Evaluation Laboratory (DEMATEL), Interpretive Structural Modeling (ISM) and Analytic Network Process (ANP). Among the identified barriers in an industrial park situated in Philippines, The method reveals the strength and direction of interaction, hierarchical network structure, prioritization of components, and the causal loop mapping to aid stakeholders in systems thinking and problem solving for such complex issues. © 2016, AIDIC Servizi S.r.l.